Biomarkers for brain disorders. Issue 4 (July 2010) - Ward, Malcolm; Schofield, Emma Louise
Biomarkers, be they genetic traits, biochemical changes or alterations in structural or functional features, are required to help the diagnosis of a variety of neurological disorders and to detect the progression of these diseases. As new medicines and therapeutic strategies are developed, biomarkers will also be required to measure the efficacy of these treatments. The importance of biomarkers in this field should not be underestimated, particularly considering the huge social and economic burden presently attributed to these diseases. This article explains the biomarker development process and aims to describe the current status of biomarker research in association with prevalent neurological disorders such as stroke, motor neuron disease, Alzheimer's disease, Parkinson's disease and Huntington's disease.